Malignant peripheral nerve sheath tumor of the descending colon with peritoneal recurrence: A case report (Indian Journal of Case Reports, 2024)
A malignant peripheral nerve sheath tumor (MPNST) is a malignant tumor devising from the peripheral nerve or displaying nerve sheath differentiation. Probably, only six cases have been reported as MPNST tumors arising in the colon. We report one such unique case of MPNST of the descending colon in a 61-year-old male who presented primarily with colicky abdominal pain for 1 month. Computed tomography (CT) showed a large mass in the descending colon. A left hemi-colectomy was performed, and a histopathological diagnosis of spindle cell sarcoma was made, which was confirmed as MPNST on immunohistochemistry (IHC). The patient again presented after 1 year with the same complaints of abdominal pain since 1 month. A CT scan revealed seven well-defined lesions in the peritoneal cavity, with the largest (8 cm) abutting the left kidney and one of the lesions abutting a small bowel segment. Exploratory laparotomy was performed with retroperitoneal mass excision and resection of the small intestine. The histopathological examination was suggestive of recurrent spindle cell sarcoma. The IHC showed S100 and CD56 positivity, which confirmed the diagnosis of recurrent MPNST.